2019
DOI: 10.1088/1742-6596/1321/2/022121
|View full text |Cite
|
Sign up to set email alerts
|

An analysis climate change of the curriculum in Indonesia

Abstract: This study aims to analyze climate change content integrates into the new geography curriculum in Indonesia. This research uses content analysis method of curriculum document consisting of basic competence and syllabus. Results represent that overall basic competence provides a huge opportunity for students to learn climate change. But the condition is not supported by the syllabus. The topics of climate change in the syllabus are a bit and also dominated by aspects of cognition of climate change. Those are se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, in all upper secondary grades, only one non-science subject-sociology-aimed to cultivate learners' sensitivity towards social issues, including climate change and global warming. Interestingly, geography subjects did not incorporate climate change as they did in the previous national curriculum 47 .…”
Section: Education Policymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in all upper secondary grades, only one non-science subject-sociology-aimed to cultivate learners' sensitivity towards social issues, including climate change and global warming. Interestingly, geography subjects did not incorporate climate change as they did in the previous national curriculum 47 .…”
Section: Education Policymentioning
confidence: 99%
“…There is no comprehensive study that investigates CCE in Indonesia holistically. Only one study by So yan and colleagues 47 delved into how climate change was incorporated into the curriculum, focusing exclusively on basic competencies-a fundamental and essential skill, knowledge, or attribute that individuals need to possess to perform effectively in a particular subject-and the syllabus of the geography subject at the upper-secondary level. Their ndings revealed that the syllabus inadequately supported the climate change learning opportunities provided by the basic competence.…”
Section: Climate Change Education In the Indonesian Contextmentioning
confidence: 99%
“…The government itself always strives to enhance and improve the quality of education in Indonesia (Hairunisya & Sunaryanto, 2020;Shufa, 2018;Sofiyan et al, 2019). "One of the efforts made by the government is to update and refine the curriculum, as the curriculum is one of the crucial components in achieving educational goals."…”
Section: Introductionmentioning
confidence: 99%
“…The student worksheets to be developed will be presented as a form of reinforcement, encompassing the same basic competencies as in the thematic book. However, the learning material within will include content based on Bondowoso's local wisdom, encompassing culture and arts, such as traditional houses (Tanean Lanjhâng), traditional attire (Kacong Jebing), and traditional dances (Tari Petik Kopi and Teri Singo Ulung) (Dewi et al, 2021;Efendi & Triaditya, 2020;Swastika et al, 2016;Winarni, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Geography education pays special attention to disaster studies because geography is an integrative discipline that brings together both the physical and human dimensions of the world in the study of people, places and environments (Mönter & Otto 2018 , Sofiyan, Aksa & Saiman 2019 ). The Lucerne Declaration on Geographical Education for Sustainable Development of 2007 emphasises the importance of risk reduction and climate change being integrated into geography teaching around the world (Haubrich, Reinfried & Schleicher 2007 ).…”
Section: Introductionmentioning
confidence: 99%